Cross-sectional descriptive study of characteristics of infants with congenital talipes equino varus requiring and not requiring tendo-Achilles tenotomy post Ponseti casting - Varute, Sharvari P.; Pundkare, Gopal; Gursale, Amey (International Journal of Research in Orthopaedics, 2025)
Background: Congenital talipes equinovarus (CTEV) is a common musculoskeletal anomaly with prevalence ranging from 0.4-7.0 per 1000 live births. The Ponseti method has revolutionized CTEV management, though percutaneous Achilles tenotomy requirements vary across populations. Objective was to evaluate characteristics of infants with CTEV requiring and not requiring tendoachilles tenotomy following Ponseti casting at an Indian tertiary care center. Methods: A prospective and retrospective cross-sectional study was conducted over 24 months (January 2022-December 2024) involving 44 children with idiopathic CTEV aged <12 months. All patients were treated using standardized Ponseti method with serial casting. Pirani scoring system assessed deformity severity. Statistical analysis compared patients requiring versus not requiring tenotomy using appropriate tests. Results: The study included 35 males (79.55%) and 9 females (20.45%) with mean age 2.70±2.47 months. Bilateral involvement occurred in 50% of cases. Mean Pirani score improved significantly from 5.55±0.70 to 0.28±0.61 (p<0.001). Ten children (22.73%) required percutaneous Achilles tenotomy while 34 (77.27%) achieved correction through casting alone. Patients requiring tenotomy had significantly higher mean age at presentation (3.5±3.27 vs 2.47±2.19 months, p=0.001), higher initial Pirani scores (5.80±0.63 vs 5.47±0.71, p<0.001), and required more casts (4.5±1.65 vs 3.85±1.33, p<0.001). Conclusions: The Ponseti method achieved 100% initial correction with relatively low tenotomy requirements (22.73%). Older age at presentation, higher initial Pirani scores, and increased casting requirements significantly predict tenotomy need. Early treatment initiation optimizes outcomes in CTEV management.